Cyber Security for the Internet of Things: A Quick Overview - K. Kishore, D. Wasiha Tasneem, R. Anil Kumar (Mathematical Statistician and Engineering Applications, 2022)
IoT has become increasingly popular in recent years. The technology is crucial. As it has gained in popularity, so have worries about its security. Since the IoT relies only on the internet, any hacker with access to the internet can find a vulnerable point in the infrastructure and steal data, possibly with the intention of keeping, erasing, or making public the stolen information. This includes all kinds of private information and data, as well as health records, intellectual property, and corporate databases. Cybersecurity prevents unauthorised access to computer systems, networks, devices, programmes, and data. Protections against cyberattacks on the Internet of Things are discussed in this study.